Dental Students' Clinical Experience Across Three Successive Curricula at One U.S. Dental School. Issue 4 (1st April 2017) - White, Joel M.; Jenson, Larry E.; Gansky, Stuart A.; Walsh, Cameron J.; Accurso, Brent T.; Vaderhobli, Ram M.; Kalenderian, Elsbeth; Walji, Muhammad F.; Cheng, Jing
Abstract : As dental schools continue to seek the most effective ways to provide clinical education for students, it is important to track the effects innovations have on students' clinical experience to allow for quantitative comparisons of various curricula. The aim of this study was to compare the impact of three successive clinical curricula on students' experience at one U.S. dental school. The three were a discipline‐based curriculum (DBC), a comprehensive care curriculum (CCC), and a procedural requirement curriculum plus externships (PRCE). Students' clinic experience data from 1992 to 2013 were analyzed for total experience and in five discipline areas. Clinic experience metrics analyzed were patient visits (PVs), relative value units (RVUs), and equivalent amounts (EQAs). A minimum experience threshold (MET) and a high experience threshold (HET) were set at one standard deviation above and below the mean for the DBC years. Students below the MET were designated as low achievers; students above the HET were designated as high achievers. The results showed significant differences among the three curricula in almost all areas of comparison: total PVs, total EQAs, total RVUs, RVUs by discipline, and number of high and low achievers in total clinical experience and by discipline. The comprehensive care approach to clinical education did not negatively impact students' clinical experience and in many cases enhanced it. The addition of externships also enhanced student total clinical experience although more study is needed to determine their effectiveness. The insights provided by this study suggest that the methodology used including the metrics of PVs, EQAs, and RVUs may be helpful for other dental schools in assessing students' clinical experience.